From Post-Communist to Anti-Canon: The Rebels - Marić, Antonela; Ćosić, Ana (Colloquia, 2024)
This paper conducts a short survey of the shift in the literary canon typical of the post-Homeland War period in Croatia. It is mainly owing to Croatian-Dalmatian authors who gathered around the magazine Feral Tribune and were inspired paradoxically by a rude, direct, and at times heavy and disturbing humour, and veristic-like scenes of everyday life, that the change happened. The shift was slow, and the authors, who were often accused of dissenting and publicly accused of activism, insisted on writing about issues other than mere patriotism, persistently succeeded in changing the mindset of the public. This would not have been possible had it not been for the political changes that took place in the country. Among other things, the paper explains the gradual appearance of the anti-canon, and argues that humour, notwithstanding the huge amount of cynical denunciations of political elites, served as a cathartic means of introspection, and a collective way of awakening from past dilemmas. Furthermore, the paper presents the situation from the 1990s to today, arguing against the hyperproduction of patriotic books, and explaining the gradual shift in the literary canon, owing to the transformation of literary practice.